THE EFFECT OF EFFORT EXPECTANCY, SOCIAL INFLUENCE, FACILITATING CONDITIONS, AND HEDONIC MOTIVATION ON THE CONTINUANCE INTENTION TO USE SHOPEEPAY MODERATED BY GENDER - Sagita, Rani; Rahmiati, Rahmiati (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The effect of effort expectancy, social influence, facilitating conditions, and hedonic motivation on the continuance intention to use ShopeePay, moderated by gender. The intention to continue using ShopeePay is explained by the continuance intention itself. Data was collected from 170 ShopeePay users in West Sumatera who participated in an online survey. Data analysis using SmartPLS revealed that the effects of effort expectancy, social influence, facilitating conditions, and hedonic motivation directly impactcontinuance intention. The findings provide evidence that gender influences effort expectancy and social influence on continuance intention. Keywords: Unified Theory Acceptance and Use of Technology;Continuance Intention; Effort Expectancy; Social Influence; Facilitating Conditions; Hedonic Motivation